If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 2 = -1 + -2x Reorder the terms: 2 + -5x = -1 + -2x Solving 2 + -5x = -1 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + -5x + 2x = -1 + -2x + 2x Combine like terms: -5x + 2x = -3x 2 + -3x = -1 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + -3x = -1 + 0 2 + -3x = -1 Add '-2' to each side of the equation. 2 + -2 + -3x = -1 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = -1 + -2 -3x = -1 + -2 Combine like terms: -1 + -2 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| f(x)=2x^2-5x+168 | | 4(2x+5)=3(x-6) | | -2n+9n-343=0 | | 10x-116=3x-11 | | 3a+5+(2a-3)= | | 7x+2+90+3x+-12=180 | | 6x+6+5x=50 | | 5x^2-29x=6 | | 3x-1=-7x+59 | | 4x+2-2x=-8 | | 5/3x+x=56 | | 12-5=n | | -3+3x=x-7 | | 7x+8=-7x+92 | | -a+3b-b+5a-6b= | | 5y+8=33 | | 10(x-8)=2x-20 | | 6=-3x+2x+5 | | 10-n=5 | | 33=x+7x+1 | | 60=-2(m+3)m | | 2x/x+4=8-8/x+4 | | 3(.75)=x | | 6x+5+5x=50 | | 12(2x-3)+5(7x-9)= | | 5x+1=-8 | | f(x)=2x^2-5x+3 | | -3-4(-1-x)=2 | | 41/5-35/6 | | y=-2/3x+3 | | 10(x-7)=7x-20 | | 34=4x+3 |